Latour Against "Freeze- Framing": A Sacred Indian "Monument" in the Anthropocene - Chatterjee, Arup K. (Implicit religion, 2023)
This paper attempts to reconsider a previously studied bulk of archival material and contemporary cultural debates, around - what is considered by a multitude of Indians as - a symbolic "monument," in the light of some of Bruno Latour's influential writings and concepts. Latour's spirit looms large in inspiring us (even in his physical absence) to redefine the secular in terms of the freedom to historicize the geological as a key to disrupting the spiritual- secular dichotomy. However, this logic works against "freeze- framing" fetishisms of bureaucratized regimes of science and religion. On the one hand, Latour's voice seems to acknowledge the need to preserve ancient lores as alternate methodologies or loose organizations of knowledge rather than as superstitious premodern confabulations. His eminent caution against blind empiricism and realism returns with a spectral force, reminding us of the dangers of deifying "matters of fact." On the other hand, Latour's reinforcement of "matters of concern" does not leave out the perils of the kind of "freeze- framing" that manifests in the case of the aforesaid Indian "monument" whenever it is hailed as a scientific reality as if to overcompensate for empiricist denials of its antiquarian values. Latour's sanity offers a desperate window across the chasm of polarized times.